Does industrial concentration impact on the relationship between policies and volatility - Moore, Winston ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2007)
Evaluates the relationship between concentration, policies and economic volatility for a sample of 147 countries for the period 1970 to 2005.